KAJIAN FAKTOR GEOGRAFI PADA PERTUMBUHAN USAHA KECIL NON PERTANIAN DI DESA BORONA DAN DESA TIBOBO KABUPATEN HALMAHERA BARAT - Alson Ungu; Grystin Djein Sumilat; Hermon Maurits Karwur (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The study of geographic factors (distance and location) is the background of this research. The objectives of this study are 1). To study geographic factors that support the growth of small non-agricultural enterprises in Borona Village and Tibobo Village, West Halmahera Regency, 2). This is to determine the contribution of small non-agricultural businesses to job opportunities in Borona Village and Tibobo Village, West Halmahera Regency. The research method is quantitative. According to the research objectives, two villages were selected that have different geographic factors (distance from the city center), namely Borona Village, Ibu District, representing villages far from Jailolo City (72 km) and Tibobo Village, Sahu District, representing villages close to Jailolo City (9 km). ). The results showed that geographic factors (distance from the city center) influenced the growth of small non-agricultural enterprises in the two research locations. Of the total 211 business units, 142 business units (67.30%) are located in Tibobo Village which is located close to the center of Jailolo City compared to Borona Village which is located far from the center of Jailolo City which only has 69 types of businesses or 32.70%. The workforce is absorbed in non-agricultural small businesses which are spread over 3 business groups consisting of 16 types of businesses and covering 211 business units.